2005
DOI: 10.1080/01443610500231435
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric risk factors for urinary incontinence and preventative pelvic floor exercises: Cohort study and nested randomized controlled trial

Abstract: We conducted a cohort study assessing risk factors for developing urinary incontinence following childbirth, and a pilot randomized controlled trial of a physiotherapist-led intervention to reduce incidence of incontinence. A total of 723 women were recruited to the cohort study, of which 234 entered the nested trial and were randomized to intensive training in pelvic floor exercises or standard information. At 6 months post-partum, 45% of women reported some incontinence problems. A pre-existing incontinence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 27 publications
4
34
2
Order By: Relevance
“…As reported by others, 8,9,26,31 the finding of this study confirmed that vaginal delivery is a significant predictor for UI. Also, in agreement with the findings of previous work that obstetric and/or gynecological surgery are significantly associated with UI, 8,28,31 teachers who had obstetric and/or gynecological surgery were more than twice as likely to experience UI as those without in this study.…”
Section: Storage Symptomssupporting
confidence: 79%
See 1 more Smart Citation
“…As reported by others, 8,9,26,31 the finding of this study confirmed that vaginal delivery is a significant predictor for UI. Also, in agreement with the findings of previous work that obstetric and/or gynecological surgery are significantly associated with UI, 8,28,31 teachers who had obstetric and/or gynecological surgery were more than twice as likely to experience UI as those without in this study.…”
Section: Storage Symptomssupporting
confidence: 79%
“…1,5,13,25,26 Procedures Institutional review board (IRB) approval was obtained from the University of North Carolina at Chapel Hill IRB for this study and the procedures are more fully described in a recent publication. 18 Twenty six elementary schools were selected from the 152 elementary schools in Taipei by using the systematic sampling method with pps and a second stage simple random sampling of 20 female teachers in each school was conducted.…”
Section: Measurementmentioning
confidence: 99%
“…This is probably due to the greater time and pressure of the pregnant uterus on pelvic suspensory (ligaments) and supporting (endopelvic fascia and muscles) structures, as suggested by other authors (25) . A previous study also demonstrated an association between constipation with postpartum UI (16) . This association is justified because constipation is related to repeated pelvic pressure and tension, occurring more often than birth (26) .…”
Section: Discussionmentioning
confidence: 96%
“…One study that assessed whether rectal distension influenced the results of a urodynamic test showed that rectal distension can cause detrusor hyperactivity in some women; however, the data were inconclusive and further research is needed (27) . A cohort study conducted six months postpartum showed that chronic constipation was a risk factor for postpartum UI (OR 1.86, CI 95% 1.03 -3.34) (16) . Another cross-sectional study conducted with non-puerperal women indicated that constipation was just as significant as obstetric trauma in causing pelvic floor problems (OR 2.35, CI 95% 1.27 -4.34) (26) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation